EFFECTS OF PROLINE-RICH PEPTIDES OF THE INNATE IMMUNE SYSTEM ON DRUG-RESISTANT BACTERIAL STRAINS - M. S. Zharkova; P. M. Kopeykin; G. E. Afinogenov; D. S. Orlov; A. Yu. Artamonov; K. E. Safiullina; M. S. Sukhareva; E. V. Tsvetkova; B. L. Milman; A. G. Afinogenova; O. V. Shamova (Медицинская иммунология)
Resistance of pathogenic microorganisms to conventional antibiotics is growing rapidly in recent years, accompanying with an increase of mortality caused by hospital-acquired infections. Therefore, a search for novel drugs to combat antibiotic resistant bacteria is one of the priorities in biomedicine. Natural compounds which are contained in host defense effector cells of humans and animals, may serve as prototypes for developing principally new antibiotics. Such compounds include antimicrobial peptides of innate immunity, in particular, a group of proline-rich peptides. The aim of this work was to evaluate antimicrobial activity of proline-rich peptides, belonging to bactenecins family, against several clinical isolates of drug-resistant Gram-negative bacteria. The bactenecins under examination (ChBac3.4, ChBac5, mini-ChBac7.5Nα, miniChBac7.5Nβ) have been previously found in leukocytes of a domestic goat Capra hircus. We have shown that chemically synthesized analogs of these peptides exhibited a pronounced in vitro antimicrobial activity against Escherichia coli and Acinetobacter baumannii (minimum inhibitory concentrations (MIC) as estimated by a broth microdilution assay varied between 1 to 4 µM) and, to a lesser degree, against Pseudomonas aeruginosa and Klebsiella pneumoniae (MIC 2-16 µM). It was revealed that antibacterial activity of these peptides may be increased if applied in combination with some conventional, antibiotics. E.g., synergistic antimicrobial effects against E. coli have been shown for mini-ChBac7.5Nα bactenecin combined with amikacin (minimal fractional inhibitory concentration index (FICI), 0.375), A. baumannii (FICI, 0.5), and K. pneumoniae (FICI, 0.325), and, using ofloxacin, towards K. pneumoniae (FICI 0.5). Lack of hemolytic activity towards human red blood cells is an important benefit of the studied peptides when used at concentrations several times higher than those showing antimicrobial effects. The data obtained presume certain prospects for further investigations of proline-rich peptides, as well as their structural modifications, for the development of new combined drugs based on these compounds, in order to combat antibiotic-resistant microorganisms, e.g., medications for local applications, various components of medical devices, in particular, venous catheters, stents and wound dressings.